2011
DOI: 10.1186/1752-2897-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective and risk factors in amateur equestrians and description of injury patterns: A retrospective data analysis and a case - control survey

Abstract: BackgroundIn Switzerland there are about 150,000 equestrians. Horse related injuries, including head and spinal injuries, are frequently treated at our level I trauma centre.ObjectivesTo analyse injury patterns, protective factors, and risk factors related to horse riding, and to define groups of safer riders and those at greater riskMethodsWe present a retrospective and a case-control survey at conducted a tertiary trauma centre in Bern, Switzerland.Injured equestrians from July 2000 - June 2006 were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 21 publications
7
40
2
Order By: Relevance
“…Similarly, a study by Smartt and Chalmers found that the oldest age‐groups displayed a high injury incidence, indicating that while most injured riders are younger, older riders also have a high risk of injury. The increased risk of injury seen in the higher age‐group is likely related to increased fragility with increased age and is consistent with previous findings that increased age is associated with higher likelihood of injury, serious injury, and fatality …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, a study by Smartt and Chalmers found that the oldest age‐groups displayed a high injury incidence, indicating that while most injured riders are younger, older riders also have a high risk of injury. The increased risk of injury seen in the higher age‐group is likely related to increased fragility with increased age and is consistent with previous findings that increased age is associated with higher likelihood of injury, serious injury, and fatality …”
Section: Discussionsupporting
confidence: 90%
“…It does appear, however, that competition riders were less frequently involved in injurious horse‐related incidents, and this could be connected to an increased level of riding proficiency or experience in horse handling. This reflects previous investigations which have found increased involvement in horse‐related injury events and injurious falls for less‐experienced riders.…”
Section: Discussionsupporting
confidence: 89%
“…Hasler reported that the most common injuries are head injuries with a percentage of 24%, followed by those of the upper extremities (17%) and the lower extremities (15%). [3] According to Silver, in contrast to other sporting accidents, there are more lumbar and thoracic injuries than cervical injuries, and more women are injured than men. Of all horse riding activities, jumping is the one most likely to cause a spinal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies confirmed that 7–10% of all riders requiring hospital admission will have a spinal injury [4, 6]. More recently Silver [4] and Hasler et al [7] reported higher incidence of spinal fractures (17% and 14% in respect). Although numerically few, catastrophic injuries to the spine and spinal cord from horse riding giving rise to paralysis have attracted considerable attention.…”
Section: Discussionmentioning
confidence: 80%
“…Greater skill and experience in equestrian sports is a contentious hypothesis of greater safety as the demands increase at the higher competitive levels [11]. Hasler et al [7] in a retrospective data analysis with a case-control study in 365 injured riders reported that older age, male gender and the possession of a diploma in horse riding can be protective factors in equestrian injuries. …”
Section: Discussionmentioning
confidence: 99%